Etika Digital: Pandangan Kritis terhadap Penggunaan Teknologi dalam Kehidupan Sehari-hari - Vera Vebriyanti; Ilma Awalya; Nindya Kartika Kusmayati (CV Edujavare Publishing, 2023)
In the increasingly connected modern era, digital technology is a major driver of social, economic, and cultural transformation. This article reviews the importance of the role of digital ethics in managing and understanding the application of technology in everyday life. Through a qualitative approach with a literature study from 2019 to 2023 and thematic analysis, this study explores the complexity of digital ethical norms, including issues such as data privacy, social media platform responsibility, and the use of artificial intelligence in decision making. This study explores the complexity of digital ethical norms, including issues such as data privacy, social media platform responsibility, and the use of artificial intelligence in decision making. The results of the analysis show that data privacy is a major focus with the increasing use of Big Data which demands stricter protection of personal data. In addition, the ethical responsibility of social media platforms is also important in facing the challenges of the spread of disinformation and manipulation of public opinion. The conclusion of this study underlines the importance of educating the public about data privacy, developing stricter policies, transparency in technology development, and international collaboration to develop global digital ethics standards. The application of digital ethics principles is expected to optimize the benefits of digital technology while minimizing risks to individuals and society as a whole.